2001
DOI: 10.1046/j.1469-0705.2001.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Ductus venosus studies in fetuses at high risk for chromosomal or heart abnormalities: relationship with nuchal translucency measurement and fetal outcome

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
112
1
11

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 22 publications
7
112
1
11
Order By: Relevance
“…As Antolin et al found, if both parameters were combined, the sensitivity decreased to 55% 7 . Furthermore, in our study, the false negative rate was 23%, with 14 fetuses with an abnormal karyotype out of 60 with an abnormal nuchal translucency measurement, but normal ductus venosus flow 6 . The real clinical value of ductus venosus Doppler seems to be the possibility to evaluate the further prognosis in terms of pregnancy outcome if nuchal translucency is increased and the karyotype is normal.…”
Section: In This Issue Ultrasound In Obstetrics and Gynecologymentioning
confidence: 88%
See 3 more Smart Citations
“…As Antolin et al found, if both parameters were combined, the sensitivity decreased to 55% 7 . Furthermore, in our study, the false negative rate was 23%, with 14 fetuses with an abnormal karyotype out of 60 with an abnormal nuchal translucency measurement, but normal ductus venosus flow 6 . The real clinical value of ductus venosus Doppler seems to be the possibility to evaluate the further prognosis in terms of pregnancy outcome if nuchal translucency is increased and the karyotype is normal.…”
Section: In This Issue Ultrasound In Obstetrics and Gynecologymentioning
confidence: 88%
“…Furthermore, there is also a significant correlation between abnormal ductus venosus waveforms and adverse outcome in chromosomally normal fetuses due to multiple congenital anomalies and unexplained intrauterine deaths 6 . There are contradictory results regarding the correlation between nuchal translucency thickness and ductus venosus pulsatility.…”
Section: In This Issue Ultrasound In Obstetrics and Gynecologymentioning
confidence: 99%
See 2 more Smart Citations
“…Los mejores resultados se obtienen entre la semana 18 y 22 de gestación (17,18), aunque hoy en día los nuevos equipos cuentan con mayor resolución, por lo que el examen se inicia a la semana 11 a la 14, donde se hace correlación con la translucencia nucal (TN) y el ductus venoso, siendo factor de riesgo para DCC tener una TN > percentil 95 o > 3,5 mm (19)(20)(21).…”
Section: Introductionunclassified